Influence of rotational speed on the statistical variability of heat penetration parameters and on the non uniformity of lethality in retort processing - Smout, C. (2000)
In a case study on white beans, the e ect of rotation on the statistical variability of heat penetration parameters and on the nonuniformity of lethality in industrial-scale retort processing was investigated. In addition, the in¯uence of process time on the nonuniformity of lethality was evaluated. No clear relation between the non-uniformity of the heating parameters and the rotational speed was observed. Rotation seemed to in¯uence process lethality variability throughout the retort by its e ect on non-uniformity in heating characteristics and in retort temperature. Absolute non-uniformity (i.e. standard deviation) increased with increasing holding time, whereas relative non-uniformity (i.e. coe cient of variation) decreased as holding time increases